The domain of the right? Explaining national parliamentary preferences on EU-related self-empowerment - Borońska-Hryniewiecka, Karolina; Sacriste, Guillaume
In the academic debate about the deficits of representative democracy in the European Union the views of members of parliaments about their EU-oriented roles remain largely unknown. Against this background, we exploit a novel dataset from an author-designed survey conducted in seven national parliaments to unravel MPs’ preferences with regard to their EU-oriented empowerment. Our findings allow to identify the dominant cognitive schemas mobilized among parliamentarians which attribute particular legitimacy-related meanings to proposed institutional reforms. They point to a stronger explanatory power of party ideological position over national constitutional orientations, with right wing parties being more supportive towards parliamentary empowerment than their centre and centre-left counterparts, and mainstream parties being more sceptical of it than radical groups on both sides of the spectrum.
Keywords: Unia Europejska; EU